Natural Dye Based-Dye Sensitized Solar Cells: A Review (Journal of Basic and Applied Research in Biomedicine, 2022)
Dye sensitized solar cells (DSSCs) is a third generation of solar cells which possess low cost of materials and fabrication process compared to silicon based solar cells added with reasonable efficiency (η).  Ruthenium (Ru)-based dye DSSC shows constant high photovoltaic performance until now, but the resource of noble metal Ru is scarce, hence their costly production. Natural dyes are interesting candidates to be applied in DSSC as an alternative dyes. Natural dyes can be produced by extraction of pigments using simple procedures from flowers, leaves, and fruits. This resource not only abundance but also easy to be attained. This paper give an overview on recent researches of the application of natural dyes in DSSC.